2018
DOI: 10.21037/jtd.2018.06.48
|View full text |Cite
|
Sign up to set email alerts
|

Tubeless major pulmonary resections

Abstract: From its inception, cutting edge minimally invasive thoracic surgery has pursued to barely produce patient perturbation. Although state of the art techniques such as uniportal approach have achieved a remarkable reduction in postoperative morbidity, there is still a way to go in patient comfort. A new 'tubeless' concept has surfaced as an alternative to double-lumen intubation with general anaesthesia combining non-intubated spontaneous breathing video-assisted thoracic surgery (VATS) surgery under locoregiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…These patients have poor respiratory reserve which makes them susceptible to pulmonary complications after GA and lung isolation due to a number of factors such as derecruitment and associated atelectrauma of the diseased lung as well as neuromuscular blockade 4. Recently, VATS has been described under monitored anesthesia care (MAC) with or without neuraxial anesthetic supplementation in an attempt to minimize these operative risks for a range of thoracic surgical procedures such as pleurodesis, blebectomy, pleural biopsies, and lung resections 5–11. Studies have demonstrated that compared with GA, in selected patient populations, non-intubated VATS improves patient satisfaction, hospital length of stay, costs, and airway complication rates such as hoarseness and sore throat 4.…”
Section: Introductionmentioning
confidence: 99%
“…These patients have poor respiratory reserve which makes them susceptible to pulmonary complications after GA and lung isolation due to a number of factors such as derecruitment and associated atelectrauma of the diseased lung as well as neuromuscular blockade 4. Recently, VATS has been described under monitored anesthesia care (MAC) with or without neuraxial anesthetic supplementation in an attempt to minimize these operative risks for a range of thoracic surgical procedures such as pleurodesis, blebectomy, pleural biopsies, and lung resections 5–11. Studies have demonstrated that compared with GA, in selected patient populations, non-intubated VATS improves patient satisfaction, hospital length of stay, costs, and airway complication rates such as hoarseness and sore throat 4.…”
Section: Introductionmentioning
confidence: 99%
“…The caution needed when referring ILD patients for surgical biopsy derives from a growing concern for the rate of mortality, ranging between 4.2% and 17.5% depending on the stratification of risk factors (10), considering the acute exacerbation of ILD after biopsy as being one of the major causes of mortality. Thus, in recent years, nonintubated VATS (NIVATS) procedures have been carried out in order to avoid the operating and anesthesiological risks of general anesthesia (GA), preserving an acceptable diagnostic and curative outcome, through the avoidance of muscle relaxants and lung injuries from positive pressure ventilation (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Its aims are to minimize the trauma and pain associated with tube interventions. enhance postoperative recovery, and hopefully make ambulatory VATS a reality (39,40).…”
Section: Discussionmentioning
confidence: 99%